The Problem of the Hypothesis in the Divided Line of Plato’s Republic - Simer Corbani, Weriquison (Sofia, 2025)
When presenting the image of the Line in Book VI of the Republic, Socrates explains that the soul progresses through four stages of investigation: supposition (εἰκασία), belief (πίστις), discursive thinking (διάνοια), and intelligence (νόησις). In the third stage, although the investigation already addresses the hypothesis of the Forms, the type of intellectual operation found at this level does not allow advancement to the next stage, which corresponds to the Form of the Good. This is because, through discursive thinking, which involves logical processes, it is impossible to reach the "principle of everything." It is therefore necessary to abandon hypothesis-based investigation and rely exclusively on another type of intellectual operation, no longer instrumental but intuitive. For this reason, only through the path of noesis, or direct vision, can one attain knowledge of the Good. This article analyzes the distinction between these two types of reasoning operations present in the Divided Line. Keywords: Hypothesis. Divided Line. Good. Plato.